Buprenorphine alters microglia and astrocytes acutely following diffuse traumatic brain injury - Jane Ryu (Nature Portfolio, 2021)
Abstract Traumatic brain injury (TBI) is a common phenomenon, accounting for significant cost and adverse health effects. While there is information about focal pathologies following TBI, knowledge of more diffuse processes is lacking, particularly regarding how analgesics affect this pathology. As buprenorphine is the most commonly used analgesic in experimental TBI models, this study investigated the acute effects of the opioid analgesic buprenorphine (Bup-SR-Lab) on diffuse neuronal/glial pathology, neuroinflammation, cell damage, and systemic physiology. We utilized a model of central fluid percussion injury (CFPI) in adult male rats treated with a single subcutaneous bolus of Bup-SR-Lab or saline 15 min post-injury. Microscopic assessments were performed at 1 day post-injury. Cell impermeable dextran was infused intraventricularly prior to sacrifice to assess neuronal membrane disruption. Axonal injury was assessed by investigating labeling of the anterogradely transported amyloid precursor protein. Neuroinflammation was assessed by analyzing Iba-1 + microglial and GFAP + astrocyte histological/morphological features as well as cytokine levels in both regions of interest (ROIs). Myelin pathology was assessed by evaluating the expression of myelin basic protein (MBP) and the propensity of MBP + myelin debris. Acute physiologic data showed no difference between groups except for reduction in weight loss following cFPI in Bup treated animals compared to saline. There were no discernable differences in axonal injury or membrane disruption between treatment groups. Cytokine levels were consistent between Bup and saline treated animals, however, microglia and astrocytes revealed region specific histological changes at 1d following Bup treatment. Myelin integrity and overall MBP expression showed no differences between Bup and saline treated animals, but there were significant regional differences in MBP expression between the cortex and thalamus. These data suggest effects of Bup treatment on weight following CFPI and potential regional specificity of Bup-associated microglial and astrocyte alterations, but very little change in other acute pathology at 1-day post-injury. Overall, this preliminary study indicates that use of Bup-SR-Lab in preclinical work does have effects on acute glial pathology, however, longer term studies will be needed to assess potential effects of Bup treatment on more chronic pathological progressions.